Recurrent convulsions, hypocalcemia, and hypoparathyroidism related to delayed diagnosis of 22q11.2 deletion syndrome in a middle‐aged man. Issue 4 (2nd May 2016) - Okazaki, Tomoya; Hifumi, Toru; Ibata, Tomohiro; Manabe, Arisa; Hamaya, Hideyuki; Yoshimoto, Takuo; Imachi, Hitomi; Murao, Koji; Kawakita, Kenya; Kuroda, Yasuhiro
Abstract : Case: A 49‐year‐old man had idiopathic epilepsy with recurrent convulsions and history of cleft palate, mental retardation, schizophrenia, and cataract. He had convulsions the day before and on the day of admission. Fosphenytoin was given i.v.; his convulsion stopped, but he lost consciousness 2 h later and was admitted. Glasgow Coma Scale score on arrival was 3. Cerebral computed tomography showed bilateral calcification in the basal ganglia. Laboratory tests showed decreased serum calcium and albumin and increased creatine kinase. He regained consciousness after i.v. calcium gluconate administration. Additionally, he showed decreased parathyroid hormone and 1, 25(OH)2 vitamin D. Suspecting hypoparathyroidism, i.v. calcium gluconate was changed to oral vitamin D. His medical history and physical appearance suggested 22q11.2 deletion syndrome, confirmed by chromosomal analysis. Outcome: The patient was discharged after 29 days and remains convulsion‐free. Conclusion: Hypocalcemia due to hypoparathyroidism should be considered in the differential diagnosis of adult recurrent convulsions.